Reconfigurable Swarms of Ferromagnetic Colloids for Enhanced Local Hyperthermia. (15th January 2018) - Wang, Ben; Chan, Kai Fung; Yu, Jiangfan; Wang, Qianqian; Yang, Lidong; Chiu, Philip Wai Yan; Zhang, Li
Abstract: Ferromagnetic particles (FMPs) have attracted a large amount of attention for tumor treatment in recent decades in the form of magnetic hyperthermia and thermoablation therapies. Previous research has commonly focused on the improvement of the specific loss power and the increase in the particle concentration to enhance the heating temperature during hyperthermia. Instead of magnetic hyperthermia with passive particles, here a feasible approach of using reconfigurable swarms of ferromagnetic colloidal particles is reported to realize enhanced local hyperthermia. The concentration of the particle swarm can be tuned up to 500% of the original particle concentration via reversible pattern transformation, i.e., shrinking and swelling. The FMP swarms with a controllable pattern size show their potential for directed energy delivery and offer a new strategy for realizing a highly localized heating effect using a low dose of the active FMPs. Abstract : A reconfigurable ferromagnetic colloidal swarm is developed for enhanced local hyperthermia. The simulation and experimental results indicate that the local heating effects and the spatial resolution of the hyperthermia process can be significantly improved by using a microrobotic swarm.